Рассказы для детей - Толстой Лев Николаевич (Школьная библиотека, 2011)
1-3 кл. Экземпляры: 4 (20200926) / Инвентарный номер: 65110 / Цена: 146.00 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Т 53 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1